PERNIKAHAN ADAT JAWA PERSPEKTIF HUKUM ISLAM - Hidayah Jaya Riswanda; Dzulfikar Rodafi; Moh. Muslim (Jurnal Hikmatina, 2021)
Almost all humans experience a stage of life called marriage. Marriage or marriage is a ceremony for the union of two souls into a family through a contract regulated by religion. Therefore, marriage becomes a great and sacred ceremony.This study examines how the perspective of Islamic law on Javanese traditional marriages is. In marriage, it has been regulated by the Shari'a which starts from the process of proposing to someone to getting married which has been explained in the Shari'a so easily. However, in the Javanese traditional tradition, there are several processions in the implementation of marriage, starting from applying to getting married. So what is the perspective of Islamic law on this matterThis research uses the type of library research, namely "a series of activities related to library data collection methods". That is by searching for data sources in the library which includes books and articles and scientific journals. This research is sourced from the law book as well as books that discuss about this research. In this study, it is about Javanese traditional marriage from the perspective of Islamic law. The researcher draws conclusions from the data that has been presented that Javanese traditional marriage is a valid Urf, which is a hereditary tradition that is carried out repeatedly by Javanese people at marriages which do not violate religious rules.Kata Kunci: Javanese traditional marriages, customs, Islamic law